2017
DOI: 10.18203/2320-1770.ijrcog20171378
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the compliance of recommended first postnatal care services utilization among reproductive age women in Benin Republic: an analysis of 2011/2012 BDHS data

Abstract: Background: High maternal and neonatal mortality persist in Benin republic. Rates of decline are slow and factors influencing PNC services utilization are not well known. This study aims to assess factors associated with PNC services utilization among mothers and their newborns with special focus on the recommendation 2 of WHO guidelines on postnatal care of the mother and the newborn.Methods: This study analysed Benin’s 2011/2012 DHS data. A total of 16,599 women were interviewed where 8,275 eligible for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
4
3
Order By: Relevance
“…Our study revealed that one-half of women received early postnatal care. This result is much higher than the levels reported in studies among postpartum women in Nepal (48), Nigeria (14), and Ethiopia (12), but lower than the 68% reported in Benin (8) and 63% in Zambia (19).…”
Section: Discussioncontrasting
confidence: 68%
“…Our study revealed that one-half of women received early postnatal care. This result is much higher than the levels reported in studies among postpartum women in Nepal (48), Nigeria (14), and Ethiopia (12), but lower than the 68% reported in Benin (8) and 63% in Zambia (19).…”
Section: Discussioncontrasting
confidence: 68%
“…Our study revealed that one-half of women received early postnatal care. This result is much higher than the levels reported in studies among postpartum women in Nepal [48], Nigeria [14], and Ethiopia [12], but lower than the 68% reported in Benin [8] and 63% in Zambia [19].…”
Section: Discussioncontrasting
confidence: 65%
“…Receiving postnatal care particularly within the first 2 days following childbirth-defined here as early postnatal care (EPNC)-is critical to the management of complications and detection of postnatal danger signs, which are necessary for protecting maternal health and averting the majority of postnatal maternal deaths [7][8][9]. Furthermore, early postnatal care offers an opportunity for women to discuss with providers healthy behaviors such as exclusive breastfeeding, proper nutrition during breastfeeding, and use of effective family planning [10], which are critical to maternal and child survival.…”
Section: Introductionmentioning
confidence: 99%
“…Early postnatal care is critical to the prevention of many complications, including: postpartum hemorrhage [ 31 , 32 ] vertical transmission of diseases [ 25 , 33 ], detection and treatment of problems and complication readiness [ 12 ]. It also allows an evaluation and the development of a personalized postnatal care plan, counseling for HIV and testing, contraception and resumption of sexual activity [ 9 , 33 ] and referral of mother and baby for special care when necessary [ 5 ].…”
Section: Introductionmentioning
confidence: 99%